Effects of fatigue on intramuscle force-stabilizing synergies - Ricotta, Joseph M.; De, Sayan D.; Nardon, Mauro; Benamati, Anna; Latash, Mark L. (Journal of applied physiology (1985), 2023)
Across multielement force production tasks, fatigue of an element leads to increased indexes of force stability (synergy indexes). Here, however, we show that groups of motor units in the tibialis anterior show decreased indexes of force-stabilizing synergies after fatiguing exercise. These findings align intramuscle synergies with spinal mechanisms, in contrast to the supraspinal control of multimuscle synergies. We applied the recently introduced concept of intramuscle synergies in spaces of motor units (MUs) to quantify indexes of such synergies in the tibialis anterior during ankle dorsiflexion force production tasks and their changes with fatigue. We hypothesized that MUs would be organized into robust groups (MU modes), which would covary across trials to stabilize force magnitude, and the indexes of such synergies would drop under fatigue. Healthy, young subjects ( n = 15; 8 females) produced cyclical, isometric dorsiflexion forces while surface electromyography was used to identify action potentials of individual MUs. Principal component analysis was used to define MU modes. The framework of the uncontrolled manifold (UCM) was used to analyze intercycle variance and compute the synergy index, ΔV Z . Cyclical force production tasks were repeated after a nonfatiguing exercise (control) and a fatiguing exercise. Across subjects, fatigue led, on average, to a 43% drop in maximal force and fewer identified MUs per subject (29.6 ± 2.1 vs. 32.4 ± 2.1). The first two MU modes accounted for 81.2 ± 0.08% of variance across conditions. Force-stabilizing synergies were present across all conditions and were diminished after fatiguing exercise (1.49 ± 0.40) but not control exercise (1.76 ± 0.75). Decreased stability after fatigue was caused by an increase in the amount of variance orthogonal to the UCM. These findings contrast with earlier studies of multieffector synergies demonstrating increased synergy index under fatigue. We interpret the results as reflections of a drop in the gain of spinal reflex loops under fatigue. The findings corroborate an earlier hypothesis on the spinal nature of intramuscle synergies. NEW & NOTEWORTHY Across multielement force production tasks, fatigue of an element leads to increased indexes of force stability (synergy indexes). Here, however, we show that groups of motor units in the tibialis anterior show decreased indexes of force-stabilizing synergies after fatiguing exercise. These findings align intramuscle synergies with spinal mechanisms, in contrast to the supraspinal control of multimuscle synergies.